PROBLEMS OF LEGAL PROTECTION AND WEBSITE PROTECTION AS AN OBJECT OF COPYRIGHT LAW - Sokolova, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to study the problems of legal protection and protection of the website as an object of copyright. Ways to overcome the problems of judicial review of disputes related to such an atypical copyright object as a website are also proposed. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to describe and propose solutions to the problem of legal protection and protection of the website as an object of copyright. Results: the website, as a rather new and atypical object of copyright, should be defined as a complex work that is created and exists with the help of different components from different fields of human creativity, each of its parts is not the main one in relation to the other, but they can be used both together and separately. However, it is most appropriate to define and provide legal protection and protection of the website as a single object of copyright at the level of legislation. Discussion: the website is an object of copyright according to the legislation of Ukraine, since it is the result of the creative work of the author and corresponds to the signs established for objects of copyright, which may contain other objects of copyright as constituent parts rights However, the website is an «untypical» object of copyright, as it also has specific features (properties) different from classic «typical» objects of copyright. It is already impossible to imagine modern life without the existence of the Internet, the development of which caused radical changes both in the global information space and in civil legal relations between their participants. The Internet has become an integral part of the life of a modern person, as it acts as a universal platform for the provision of various services, both informational and commercial, due to which some satisfy their needs, while others receive income. In this regard, the number of information resources is increasing, in particular, new ones are being created websites, and therefore questions inevitably arise regarding the protection of various objects of intellectual property law and, in particular, objects of copyright, because they have both a creative and a technical component. But the issues of legal protection and protection of such objects still remain insufficiently researched from a legal point of view.